2020
DOI: 10.1007/s00428-020-02798-5
|View full text |Cite
|
Sign up to set email alerts
|

MAML2 rearrangement as a useful diagnostic marker discriminating between Warthin tumour and Warthin-like mucoepidermoid carcinoma

Abstract: Warthin tumour is the second most common benign neoplasm of salivary glands. Despite its relatively characteristic histology, it may sometimes mimic other lesions. Here, we report two female non-smoker patients diagnosed with low-grade mucoepidermoid carcinoma with oncocytic epithelium and prominent lymphoid (Warthin-like) stroma and with molecularly confirmed MAML2 rearrangement. In addition, we screened a consecutive series of 114 Warthin tumour cases by means of MAML2 break apart fluorescence in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Radiological features were available for nine cases: Ultrasonography (9,11) and computed tomography (8,10,15) revealed a well-circumscribed tumour with multiple cysts. Magnetic resonance imaging displayed a low-or intermediate-intensity tumour (10)(11)(12)15). These features are consistent with those of conventional low-grade MEC (16).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Radiological features were available for nine cases: Ultrasonography (9,11) and computed tomography (8,10,15) revealed a well-circumscribed tumour with multiple cysts. Magnetic resonance imaging displayed a low-or intermediate-intensity tumour (10)(11)(12)15). These features are consistent with those of conventional low-grade MEC (16).…”
Section: Discussionsupporting
confidence: 74%
“…The present study reported the sixth cytological Warthin-like MEC case. To the best of our knowledge, only 22 cases, including the present case, have been reported since the first report by Ishibashi et al (3) in 2015 (8)(9)(10)(11)(12)(13)(14)(15). Table I summarizes the clinicopathological features of Warthin-like MEC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Microscopic foci of the conventional mucoepidermoid carcinoma exhibiting epidermoid and intermediate cells are often present and their identification aids in making the current diagnosis. In equivocal cases, the presence of a MAML2 rearrangement confirms the malignant diagnosis [24,25]. Another differential diagnosis of a WT includes oncocytoma and nodular oncocytic hyperplasia.…”
Section: Diagnostic Pathologymentioning
confidence: 90%
“…Both fusion products and EGF expression are used for diagnostic purposes to predict the outcome of the disease. FISH analysis of MALM2 rearrangement has been used to identify MEC in histological samples that strongly resembled Warthin’s tumor [ 81 , 82 ]. Chromosomal rearrangements have also been described in pleomorphic adenoma, such as the reciprocal translocations t (3;8) (p21;q12) resulting in promoter swapping between the zinc finger PLAG1 and the β-catenin gene [ 83 ].…”
Section: Cellular and Molecular Mechanisms At The Origin Of Salivamentioning
confidence: 99%